Improvement of the Volatile Components of Cork from Quercus suber L. by an Autoclaving Procedure - Rocha, Sílvia; Delgadillo, Ivonne; Ferrer Correia, A J (Journal of Agricultural and Food Chemistry, 1996)
The volatiles of cork slabs submitted to a novel industrial treatment, autoclaving, were compared with the volatiles of the untreated slabs to establish the usefulness of this treatment as a cleanup procedure. The condensed steams corresponding to the first and a second autoclaving process were also analyzed. The volatile compounds of cork and of autoclaved condensed steam were extracted by simultaneous distillation?extraction and analyzed by gas chromatography and combined gas chromatography?high-resolution mass spectrometry. Cork slabs treated with steam under pressure showed smaller amounts of the volatile components with musty, moldy, and related odors, such as 3-methyl-1-butanol, 1-octanol, and guaiacol and other mold metabolites. The condensed steam contained compounds corresponding to those extracted from the cork. The autoclaving process has potential for industrial use to clean the cork and to reduce volatiles of microbial origin in cork samples. Keywords: Quercus suber L.; volatiles; autoclaving process; condensed steam; musty and moldy odors
doi: 10.1021/jf950041s
Keywords: autoclaving process; condensed steam; musty and moldy odors; Quercus suber L.; volatiles